Primary abdominal pregnancy causing diagnostic dilemma: a case report - Sandhya Gadre; Sonal Jain; Chaudhary, Gunjan; Farah Meenai Jalaly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The aim of the study was to present a case of primary abdominal pregnancy, a rare entity and highlighting the diagnostic dilemma and importance of surgical management. Primigravida with an amenorrhea of 35 days presented to the casualty with acute abdomen, with faintly positive UPT test and USG pelvis was suggestive of ill-defined hypoechoeic mass lesion in right sided adnexal region abutting right ovary. Intra-operatively, blood clots with products of conception were found adherent to anterior layer of right broad ligament. Uterus, both fallopian tubes and both ovaries found intact with normal morphology. On histopathology, no chorionic villi was found inside the lumen of the fallopian tube. Presence of occasional ghost chorionic villi embedded in blood clots, scattered cytotrophoblast and syncytiotrophoblasts also seen in the sample obtained from the anterior leaf of broad ligament. Primary abdominal pregnancy is not only rare but the diagnosis is also a challenge. It can be diagnosed conclusively after laparotomy. There are no symptoms which are pathognomonic for abdominal pregnancy. The symptoms are akin to other types of ectopic pregnancy, so a high index of suspicion is highly necessary for diagnosis. The keys to management are an early diagnosis and prompt surgery.